A Slow Orthostatic Tremor of Primary Origin - Coffeng, Sophie M. (Columbia University Libraries/Information Services, 2013)
BACKGROUND: Orthostatic tremor (OT) is a high-frequency tremor (13–18 Hz) present in the legs when standing. Underlying disease is found in one-third of OT patients. CASE REPORT: We describe an 86-year-old man with progressive shaking of the legs while standing, which disappears immediately after sitting down or while walking. Polymyography confirmed a tremor of the legs (10–11 Hz) while standing. Magnetic resonance imaging (MRI) and neurologic examination showed no underlying disease. DISCUSSION: Primary OT can appear at a lower frequency of 10–11 Hz.